1972
DOI: 10.1677/joe.0.0550079
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis After Oophorectomy in the Mature Female Rat and the Effect of Oestrogen and/or Progestogen Replacement Therapy in Its Prevention

Abstract: SUMMARY Fifty-two mature female rats on a controlled diet were studied to compare the effects of oophorectomy, and hormone replacement therapy after oophorectomy, on femoral morphology and mineral content. Oophorectomy was followed by the development of osteoporosis after 11 months of observation. This was characterized by a reduction in ash per unit length of bone and a diminution of mid-shaft femoral cortical width. The administration of a progestogen (9 μg ethynodiol diacetate/rat/day) for 10 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
2

Year Published

1983
1983
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(40 citation statements)
references
References 0 publications
3
35
2
Order By: Relevance
“…The reduction in plasma calcium concentration and the bone calcium content after ovariectomy was consistent with the findings of Saville (1965) Aitken (1972) and Cruess and Hong (1979). How ovariectomy led to hypocalcemia is not yet clear but a suppression of GI calcium absorption and serum 1,25(OH)2D3 was reported in postmenopausal women (Riggs et al, 1981).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in plasma calcium concentration and the bone calcium content after ovariectomy was consistent with the findings of Saville (1965) Aitken (1972) and Cruess and Hong (1979). How ovariectomy led to hypocalcemia is not yet clear but a suppression of GI calcium absorption and serum 1,25(OH)2D3 was reported in postmenopausal women (Riggs et al, 1981).…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that rats develop osteopenia after ovariectomy (OVX),' and the OVX rat has been used as a model for postmenopausal osteoporosis (1)(2)(3). Our studies have shown that bone density in rats is reduced 6 mo post-OVX, and that the ratio of femoral cortical thickness to midshaft diameter was significantly lower than normal (x-ray femoral score; Table I).…”
Section: Introductionmentioning
confidence: 57%
“…Ovariectomy causes osteopenia in rats (22)(23)(24)(25)(26)(27) and has been used as a model for postmenopausal bone loss (25)(26)(27). Wronski et al (27) reported osteopenia and increased bone resorption and formation, estimated by histomorphometry, as early as 14 days after ovariectomy.…”
Section: Discussionmentioning
confidence: 99%